Model Cakar Sebagai Media Edukasi Terhadap Peningkatan Perilaku Remaja dalam Pencegahan Karang Gigi - Siti Adlinah Fatman; Lanny Sunarjo; Diyah Fatmasari; Kusno Kusno (Syntax Corporation Indonesia, 2023)
Based on RISKESDAS data for 2018, 57.6% of people in Indonesia have dental and oral health problems. Meanwhile, in the province of Central Java, dental and oral health problems reached 56.66% and only 9.02% received treatment. In the city of Semarang, dental and oral health problems reached 48.38% and only 14.22% received treatment. Dental health problems in adolescents are not much different from dental and oral health problems in children and adults. There are many ways that can be done to overcome these problems including the use of multimedia as an educational medium. The use of Augmented Reality has proven effective in increasing student learning interest. Proving the effectiveness of applying the CAKAR model (Augmented Reality Tartar Disc) as an educational medium in increasing changes in adolescent behavior in preventing tartar. The method used is Research and Development with a Quasy experiment Pretest-Posttest group design research design. The